2018
DOI: 10.1002/adsc.201701615
|View full text |Cite
|
Sign up to set email alerts
|

N‐(Acyloxy)phthalimides as Redox‐Active Esters in Cross‐Coupling Reactions

Abstract: Recent years have witnessed a resurgence of novel, efficient and practical protocols for radical‐mediated cross‐coupling reactions involving N‐(acyloxy)phthalimides (NHPI esters) as redox‐active esters. After the initial discovery of the redox‐active properties of NHPI esters, exciting examples of SET‐based cross‐coupling reactions under thermal or photolytic conditions leading to diverse C–X (X=C, B, Si, Se, S) bonds have been published. The operational simplicity and broad applicability exhibited in redox‐ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
198
1
5

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 374 publications
(205 citation statements)
references
References 106 publications
1
198
1
5
Order By: Relevance
“…[3] Besides the atom-and step-economic methods to utilize carboxylic acids directly, [4] the traceless activation group strategy that uses N-(acyloxy)phthalimide (socalled redox active esters or RAEs), [5] which can be easily installed through condensation reaction, [5c] offered the other convenient way to perform various decarboxylative transformations. [6] The majority of the developed methodologies for decarboxylative carboncarbon bond formation utilized either transition-metal complexes as catalyst under thermal condition [7] or photoredox catalysts [8] to activate RAEs, especially for COMMUNICATIONS [a] Reaction condition: olefines (0.2 mmol), RAEs (0.3 mmol), HE (0.3 mmol) in DMA (2 mL), irradiated by 40 W blue LEDs (456 nm) at room temperature for 12 h under argon atmosphere. Yield of isolated product.…”
mentioning
confidence: 99%
“…[3] Besides the atom-and step-economic methods to utilize carboxylic acids directly, [4] the traceless activation group strategy that uses N-(acyloxy)phthalimide (socalled redox active esters or RAEs), [5] which can be easily installed through condensation reaction, [5c] offered the other convenient way to perform various decarboxylative transformations. [6] The majority of the developed methodologies for decarboxylative carboncarbon bond formation utilized either transition-metal complexes as catalyst under thermal condition [7] or photoredox catalysts [8] to activate RAEs, especially for COMMUNICATIONS [a] Reaction condition: olefines (0.2 mmol), RAEs (0.3 mmol), HE (0.3 mmol) in DMA (2 mL), irradiated by 40 W blue LEDs (456 nm) at room temperature for 12 h under argon atmosphere. Yield of isolated product.…”
mentioning
confidence: 99%
“…In this regard, visible light‐mediated photoredox catalysis represents a powerful alternative and environment‐friendly tool in fostering of modern synthetic chemistry . Additionally, it has recently been revealed that redox‐active N ‐(acyloxy)phthalimides (NHPI esters) participate in an exciting range of single electron transfer (SET)‐based cross‐coupling reactions under photolytic conditions . NHPI esters are bench stable and readily available feedstock that can easily be prepared from the corresponding carboxylic acids and N ‐hydroxyphthalimide under standard coupling conditions .…”
Section: Figurementioning
confidence: 99%
“…Such a visible photoredox catalysis driven tandem radical strategy would be highly efficient and fascinating from the perspective of green chemistry. As part of our ongoing program on photoredox catalysis and driven by our interest in N ‐(acyloxy)phthalimides as redox‐active esters, we herein disclose a hitherto unknown Eosin Y catalyzed cascade radical annulation of NHPI esters and 2‐(allyloxy)arylaldehydes to yield 3‐alkyl substituted chroman‐4‐ones under visible light irradiation (Scheme c).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Shang, Fu und Wang [31] sowie die Gruppe von Glorius [32] entdeckten 2018 unabhängig voneinander,d ass ein photoangeregter Pd 0 -Komplex einen SET mit aliphatischen N-(Acyloxy)phthalimiden 61 (redoxaktiven Estern [33] Die photoangeregte Pd-Katalyse wurde bisher in Alkyl-Heck-Reaktionen und C-H-Aktivierungen angewendet. Shang, Fu und Wang [31] sowie die Gruppe von Glorius [32] entdeckten 2018 unabhängig voneinander,d ass ein photoangeregter Pd 0 -Komplex einen SET mit aliphatischen N-(Acyloxy)phthalimiden 61 (redoxaktiven Estern [33] Die photoangeregte Pd-Katalyse wurde bisher in Alkyl-Heck-Reaktionen und C-H-Aktivierungen angewendet.…”
Section: Angewandte Chemieunclassified